sin ( θ 1 ) + sin ( θ 2 ) + sin ( θ 3 ) = cos ( θ 1 ) + cos ( θ 2 ) + cos ( θ 3 ) = 0 sin 2 ( θ 1 ) + sin 2 ( θ 2 ) + sin 2 ( θ 3 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
But how do you know that this value must be true for all possible sets of θ i that satisfy the conditions?
Good solution sir +1
In the note (Argand Diagram and Sum of Cosines of Multiple Angle = 1/2), I showed that for sin θ 1 + sin θ 2 + sin θ 3 = cos θ 1 + cos θ 2 + cos θ 3 = 0 , which is equivalent to a balanced mechanical system, the three numbers (analogous to "rods") must be symmetrically distributed. In this case 1 2 0 ∘ apart, otherwise the system is imbalanced or sin θ 1 + sin θ 2 + sin θ 3 = 0 or cos θ 1 + cos θ 2 + cos θ 3 = 0 or both = 0 . Therefore, θ + 3 2 k π , where k = 0 , 1 , 2 represent all possible sets of θ i .
Notation: sin θ n = S n , cos θ n = C n
Now, S 1 + S 2 + S 3 = 0 = C 1 + C 2 + C 3
Squaring both sides,
⇒ S 1 2 + S 2 2 + S 3 2 + 2 ( S 1 S 2 + S 2 S 3 + S 3 S 1 ) = 0 . . . . ( 1 ) , and C 1 2 + C 2 2 + C 3 2 + 2 ( C 1 C 2 + C 2 C 3 + C 3 C 1 ) = 0 . . . . ( 2 )
Adding ( 1 ) and ( 2 ) and solving further, ⇒ 3 + 2 ( S 1 S 2 + C 1 C 2 + S 2 S 3 + C 2 C 3 + S 3 S 1 + C 3 C 1 ) = 0 ⇒ cos ( θ 1 − θ 2 ) + cos ( θ 2 − θ 3 ) + cos ( θ 3 − θ 1 ) = 2 − 3
Now on the right side 2 − 3 reminds us of 3 × cos 3 2 π . So we know one such solution set. Based on the observation, we can assume WLOG that
θ 1 = 2 n π
θ 2 = θ 1 + 3 2 π
θ 3 = θ 1 − 3 2 π
Therefore one of the solution set is θ 1 = 0 , θ 2 = 3 2 π , θ 3 = − 3 2 π , ⇒ sin 2 ( θ 1 ) + sin 2 ( θ 2 ) + sin 2 ( θ 3 ) = 2 3
A tricky solution:
Choose θ 1 = − 3 2 π , θ 2 = 0 , θ 3 = 3 2 π , we get: sin 2 ( θ 1 ) + sin 2 ( θ 2 ) + sin 2 ( θ 3 ) = 2 3
Problem Loading...
Note Loading...
Set Loading...
The general solution of the equations is as follows (see note ):
{ sin θ 1 + sin θ 2 + sin θ 3 = 0 cos θ 1 + cos θ 2 + cos θ 3 = 0 ⇒ ⎩ ⎪ ⎨ ⎪ ⎧ θ 1 = θ θ 2 = θ + 3 2 π θ 3 = θ + 3 4 π = θ − 3 2 π
Proof:
sin θ 1 + sin θ 2 + sin θ 3 = sin θ + sin ( θ + 3 2 π ) + sin ( θ − 3 2 π ) = sin θ − 2 1 sin θ + 2 3 cos θ − 2 1 sin θ − 2 3 cos θ = 0
cos θ 1 + cos θ 2 + cos θ 3 = cos θ + cos ( θ + 3 2 π ) + cos ( θ − 3 2 π ) = cos θ − 2 1 cos θ − 2 3 sin θ − 2 1 cos θ + 2 3 sin θ = 0
Now, we have:
sin 2 θ 1 + sin 2 θ 2 + sin 2 θ 3 = ( sin θ 1 + sin θ 2 + sin θ 3 ) 2 − 2 ( sin θ 1 sin θ 2 + sin θ 2 sin θ 3 + sin θ 3 sin θ 1 ) = 0 − 2 [ sin θ sin ( θ + 3 2 π ) + sin ( θ + 3 2 π ) sin ( θ − 3 2 π ) + sin ( θ − 3 2 π ) sin θ ] = − 2 [ sin θ ( − 2 1 sin θ + 2 3 cos θ − 2 1 sin θ − 2 3 cos θ ) + ( − 2 1 sin θ + 2 3 cos θ ) ( − 2 1 sin θ − 2 3 cos θ ) ] = − 2 [ − sin 2 θ + 4 1 sin 2 θ − 4 3 cos 2 θ ] = 2 [ 4 3 sin 2 θ + 4 3 cos 2 θ ] = 2 3 = 1 . 5